A Randomized, Triple-Blind, Placebo-Controlled, Add-On Clinical Trial to Evaluate the Efficacy of Emblica officinalis in Uncontrolled Hypertension. (7th October 2020) - Ghaffari, Samad; Navabzadeh, Maryam; Ziaee, Mojtaba; Ghobadi, Ali; Ghods, Roshanak; Hashem-Dabaghian, Fataneh
Abstract : Introduction. Emblica officinalis (EO) has some cardiovascular effects, and there are some animal studies that show its antihypertensive effect. This study was conducted to determine the effect of combination of EO with standard therapy on the systolic blood pressure (SBP) and diastolic blood pressure (DBP) in patients with uncontrolled hypertension. Materials and Methods. This was a randomized, triple-blind, placebo-controlled, 8-week study. Ninety-two patients with uncontrolled hypertension despite taking hypotensive drugs were randomly assigned into two groups to take EO (500 mg/TDS after meal) or placebo in combination with standard antihypertensive drugs. After 2, 4, 6, and 8 weeks of intervention, SBP and DBP and heart rate (HR) were measured. Data were analyzed by SPSS software using repeated measures ANOVA. Results. Eighty-one patients (41 in the drug group and 40 in the placebo group) completed the study for 8 weeks and were analyzed. The mean ± standard deviation of age was 53.64 ± 10.01 years. SBP decreased as 15.6 ± 8.23% in the EO group and 6.3 ± 7.49% in the placebo group (P < 0.001 ). DBP decreased as 12.3 ± 7.87% and 3.88 ± 7.98%, respectively (P < 0.001 ). Time effect was not significant, but the group effect was significant ( F = 13.875, P = 0.001 for systolic BP and F = 18.948, P < 0.001 for diastolic BP) . No side effects were reported during the study. Conclusion. Eight-week combination therapy of EO with standard antihypertensive drugs significantly reduced the SBP and DBP more than placebo in patients with uncontrolled hypertension.